2005
DOI: 10.1081/cbi-200062407
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐Day Effect on the Torque and Neuromuscular Properties of Dominant and Non‐Dominant Quadriceps Femoris

Abstract: The study was conducted first, to determine the possibility of a dichotomy between circadian rhythm of maximal torque production of the knee extensors of the dominant and non-dominant legs, and second, to determine whether the possible dichotomy could be linked to a change in the downward drive of the central nervous system and/or to phenomena prevailing at the muscular level. The dominant leg was defined as the one with which subjects spontaneously kick a football. Tests were performed at 06:00, 10:00, 14:00,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
107
3
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 38 publications
(48 reference statements)
21
107
3
6
Order By: Relevance
“…Even though it is still largely accepted that temperature is the primary circadian indicator of physical performance, recent evidence has challenged the traditional views about the relationship between body temperature and exercise performance. Recent studies investigating the neuromuscular performance at different timeof-day revealed a distinct circadian rhythm in physiological variables independent of temperature changes (Guette et al, 2005). This can explain the fact that circadian rhythm in sporting performance is affected by multi-factorial mechanisms, such as time since waking, level of fatigue, alertness (Atkinson et al, 1998;Edwards et al, 2007) and mood state (Drust et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though it is still largely accepted that temperature is the primary circadian indicator of physical performance, recent evidence has challenged the traditional views about the relationship between body temperature and exercise performance. Recent studies investigating the neuromuscular performance at different timeof-day revealed a distinct circadian rhythm in physiological variables independent of temperature changes (Guette et al, 2005). This can explain the fact that circadian rhythm in sporting performance is affected by multi-factorial mechanisms, such as time since waking, level of fatigue, alertness (Atkinson et al, 1998;Edwards et al, 2007) and mood state (Drust et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The worst performance of dribbling and agility observed in the morning can be explained by the significant low body-temperature (P < 0.01) which can modify muscular electric activity, causing a change in muscular coordination and, consequently, a performance decrease (Oksa et al, 1996). Moreover, the effect of time of day on muscle contractile properties could be attributed, in part, to an intracellular variation in the muscle (e.g., a circadian variation in inorganic phosphate concentration) and/or, in part, to the circadian rhythm in the central temperature, which could influence calcium release by the sarcoplasmic reticulum (Guette et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It must, however, be noted that their study was not primarily designed to address the effect of time of day. Hence, the acute loadings and biopsy samplings were not scheduled to early morning and late afternoon hours, when diurnal minimum and maximum in neuromuscular performance is typically found, respectively (12,26,32,33,35). Furthermore, early morning and late afternoon hours are also when hormonal signalling is dramatically different (e.g., cortisol to testosterone ratio -for a review see (16)).…”
Section: Introductionmentioning
confidence: 99%
“…Another contributing factor to strength testing is the time of day effect when maximal muscle contractions are influenced by the circadian fluctuations in muscle temperature that occur throughout the day with a 10% positive difference having been observed in an evening when compared to the morning within the same subjects [25]. In contrast, Gribble et al [26] reported better SEBT performance in a morning compared to afternoon or evening.…”
Section: Discussionmentioning
confidence: 87%